Building capacities for inclusive and sustainable agricultural and rural development in Southeast Asia - Quimbo, Maria Ana T.; Sulabo, Evangeline C. (2015)
As the Southeast Asia Regional Center for Graduate Study and research in Agriculture (SEARCA) approaches its 50th founding anniversary, it continues to pursue its mission of strengthening the capacities of Southeast Asia leaders and institutions under its reformulated mission of Inclusive and Sustainable Agricultural and Rural Development (ISARD). Guided by this mission, this study analyzed the desired and priority capacity development needs of institution heads and key personnel toward addressing the constraints, problems, and issues related to agricultural and rural development toward achieving their institutional goals.
Adopting an exploratory, descriptive research design, the study examined the competency needs at the institutional and personnel levels. A total of 35 institution heads from seven countries and 40 key personnel from eight countries served as research participants. The results showed a variety of competencies in the areas of leadership and management; agriculture; climate change; research, monitoring, and evaluation; planning, and extension or community service. While mismatch was found in a number of desired and prioritized competency areas perceived by the respondents, there were also interesting convergent answers in both technical and non-technical areas. Interestingly, both the desired and prioritized competency needs were a combination of "hard" skills and "soft" skills. Hard skills refer to technical skills learned through formal education or gained from years of experience. On the other hand, soft skills are not necessarily learned through formal training, are less tangible, and refer to interpersonal skills.
Policy recommendations were forwarded on the need to continue building capacities in core competencies along ISARD; have a balance of "hard" skills and "soft" skills through the use of appropriate training strategies and explicit statement in training objectives; strengthen awareness on "soft" skills through its integration in workplace culture; build capacity on action research; continue partnerships; encourage mentoring; prioritize competencies; and build capacity of desired and priority competency areas.
Keywords: Sustainable development -- Southeast Asia; Capacity building; Training evaluation